A role for IRF8 in B cell anergy - Pathak, Simanta (2013)
B cell central tolerance is a process through which self-reactive B cells are removed from the B cell repertoire. Self-reactive B cells are generally removed by receptor editing in the bone marrow and by anergy induction in the periphery. Interferon regulatory factor 8 (IRF8) is a critical transcriptional regulator of immune system development and function. A recent study has shown that marginal zone B cells and B1 B cells population are dramatically increased in the IRF8 deficient mice, indicating that there are B cell developmental defects in the absence of IRF8. Here, we report that mice deficient for IRF8 produced anti-dsDNA antibodies. Using hen egg lysozyme double transgenic model, we further demonstrate that B cell anergy was breached in the IRF8 deficient mice. While anergic B cells in the IRF8 proficient background were blocked at the transitional stage of development, anergic B cells in the IRF8 deficient background were able to further mature which allow them to regain responses to antigen stimulation. Interestingly, our results show that IRF8 deficient B cells were more sensitive to antigen stimulation and were resistant to antigen induced cell death. Moreover, our results show that IRF8 was expressed at a high level in the anergic B cells and elevated level of IRF8 promoted apoptosis in the transitional B cells. Thus, our findings presented here reveal a previously unrecognized function of IRF8 in B cell anergy induction.